THE EFFECT OF ENDORPHIN MASSAGE AND WARM COMPRESSES ON THE INTENSITY OF LOW BACK PAIN IN THIRD TRIMESTER PREGNANT WOMEN - Nuraeni, Rani; Februanti, Sofia; Adini, Syaukia (Media Informasi, 2025)
Background: Lower back pain is joint among pregnant women, especially in the third trimester, affecting around 70% in Indonesia. This discomfort significantly impacts daily activities and quality of life. Endorphin massage, a light touch technique that stimulates the release of the body's natural pain-relief hormones, and warm compresses, which use heat to reduce pain, are two methods to address this issue. This study aimed to evaluate the effect of these methods on lower back pain intensity in third-trimester pregnant women. Using a quasi-experimental design with a one-group pre-test post-test approach, 15 pregnant women were selected from a population of 51 through purposive sampling. Pain intensity was measured on the first and third days using the Numeric Rating Scale (NRS). Results showed a significant reduction in pain intensity, from an average of 5.40 before the intervention to 1.60 after. A paired sample T-test yielded a p-value of 0.000, indicating a significant effect of endorphin massage and warm compresses on reducing lower back pain in third-trimester pregnant women at the Karikil Community Health Center Work Area